2008
DOI: 10.1902/jop.2008.080057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Menstrual Cycle on the Oral Microbial Flora in Women: A Case‐Control Study Including Men as Control Subjects

Abstract: During a menstruation period, cyclic variation in the subgingival microbiota of periodontally healthy women of child-bearing age who were not using oral hormonal contraceptives could not be confirmed. Male control subjects presented with higher levels of many species but also without a cyclic pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
0
23
0
2
Order By: Relevance
“…The prevalence of smoking in Jordanian men is reported to be in the range of 56.9–62% compared to 11.0–11.4% in women [29, 30]. The effect of gender on the subgingival bacterial flora is controversial; several studies conducted on periodontitis patients have reported a difference in the bacterial profile between males and females [31, 32], while other studies have reported that gender has no effect on the subgingival bacterial profile in CP patients or in healthy controls [33, 34]. The PPD was significantly higher in healthy non-smokers compared to smokers; this increase is most likely related to increased age among the non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smoking in Jordanian men is reported to be in the range of 56.9–62% compared to 11.0–11.4% in women [29, 30]. The effect of gender on the subgingival bacterial flora is controversial; several studies conducted on periodontitis patients have reported a difference in the bacterial profile between males and females [31, 32], while other studies have reported that gender has no effect on the subgingival bacterial profile in CP patients or in healthy controls [33, 34]. The PPD was significantly higher in healthy non-smokers compared to smokers; this increase is most likely related to increased age among the non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between female sex hormone levels and periodontal changes during puberty, pregnancy, and menopause has been postulated, but there are a limited number of studies investigating the effects of menstrual cycle on periodontal health 10,16 . The changes in gingival tissues occurring during menstrual phases of women could be related to the changes in inflammatory markers in gingival crevicular fluid (GCF).…”
mentioning
confidence: 99%
“…Interestingly, the levels of Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans ) reportedly increased between the onset of menstruation and 2 weeks ( P <0.05). These differences were not significant at the P <0.001 level set in the aforementioned study 13 …”
mentioning
confidence: 62%
“…Such polymorphonucleocyte hormonal‐induced impairment may translate into gingival inflammation 12 . A recent study 13 could not confirm a specific cyclic pattern of bacterial colonization in a group of 20 systemically and periodontally healthy females who were not taking OCs during one full menstrual cycle. Interestingly, the levels of Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans ) reportedly increased between the onset of menstruation and 2 weeks ( P <0.05).…”
mentioning
confidence: 96%